Um panorama da literatura sobre a internacionalização das religiões ayahuasqueiras brasileiras - Glauber Loures Assis; Beatriz Caiuby Labate (Ciências Sociais Unisinos)
Created during the twentieth century, Barquinha, Santo Daime, and the União do Vegetal, known as the Brazilian ayahuasca religions, were circumscribed to the northern region of Brazil at least until the beginning of the 1970s. Since then, Santo Daime and the União do Vegetal have expanded significantly, each one in its own way, reaching all the regions of the country, crossing the Brazilian borders and the Atlantic Ocean. The process of internationalization of these groups involves complex nets and transnational alliances, generating intriguing issues on cultural translation and religious diaspora. Nevertheless, the theme is rarely explored and the information is widely scattered. This article proposes a critical review of the academic literature on the internationalization of these groups, including articles, master’s theses and doctoral dissertations in various languages, published or not, as well as texts on the legal aspects. Through a comparative approach, we seek to identify the main characteristics, tendencies, and perspectives of the ayahuasca field of studies. In this way, we hope to call attention to the possibilities and gaps of this discussion and, at the same time, stimulate the development of more research. This article aims to become a sort of guide to the researchers in this area as well as to be of use to others interested in the subject. The internationalization of the ayahuasca religions has already reached dozens of countries in the world, and offers an interesting locus of study of the interaction among psychedelics, culture, language, and cognition.